Propane clusters in Titan's lower atmosphere: insights from a combined theory/laboratory study. Issue 1 (26th June 2019) - Bourgalais, J; Durif, O; Le Picard, S D; Lavvas, P; Calvo, F; Klippenstein, S J; Biennier, L
ABSTRACT: In spite of the considerable advances made by Cassini – Huygens in our understanding of Titan, many questions endure. In particular, the detailed processes that lead to the formation of haze aerosols in Titan's atmosphere, found in high concentrations at low altitudes, are not well identified. Hydrocarbons, which are abundant constituents of Titan's cold atmosphere originating from photochemical processes, may simultaneously condense on the surface of existing aerosols, nucleate and grow to generate new aerosol seeds. The relative importance of the various processes depends on several factors, including the saturation ratio. The dynamics of hydrocarbon condensation and nucleation in Titan's atmosphere remains poorly known. Aiming to progress on these issues, we investigate here the kinetics of propane dimer formation at low temperature through state-of-the-art laboratory experiments combined with theoretical calculations. Our results provide an estimate of the rate coefficients, which are then employed to evaluate the abundance of propane dimers in the lower atmosphere of Titan. The mixing ratios of propane dimers inferred, with a maximum abundance of 10 cm −3 near 100 km, is found to be under the detection limit of the Composite Infrared Spectrometer of the Cassini spacecraft. Based on our results, homogeneous nucleation of the most abundant species appears not to be relevant for the growth of aerosols. Future studies should focus on homogeneous nucleation of polar molecules or alternatively on heterogeneous processes, which are usually more efficient.